STUDI FENOMENOLOGI : KETEPATAN PEMBERIAN OPINI OLEH KANTOR AKUNTAN PUBLIK DI MAKASSAR - Irfansyah Fahmi; Fadliah Nasaruddin; Asriani Djunaid (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
The Phenomological Study of the Accuration of Giving Opinion by the Public Accounting Firm in Makassar The purpose of this study is to analyze the accuracy of giving opinions by the Accounting Firm (KAP) to the companies. The data used are primary data collected through the dissemination of interviews to each informant. Population in this study is the auditors who work at public accounting firm in Makassar. The method used is qualitative with phenomenology approach. The results showed that (1)The KAP in carrying out tasks always done by professional persons. (2)The KAP in carrying out the duties always follow the audit procedures. (3)Whatever opinions are issued by the KAP that has been done audit procedures based on SPAP, then the result is right.